Finance Art: On the Secret Life of Global Finance - Dossou, Stephanie Anne (Trinity College Dublin. School of Computer Science & Statistics. Discipline of Computer Science, 2022)
While the impact of global finance and financialization can be seen everywhere, those machines themselves might appear abstract, complex, and difficult to grasp. Their connections with everyday life have become invisible through the multiple levels of abstraction that have been created between the real economy and financial markets, as well as commodities and financial instruments. Global finance and the process of financialization have become prevalent at a macro level through globalisation, the disproportional dominance of this sector in the global economy, and the effects they have on society. They also have a large impact at a micro level through their infiltration into people s everyday life, forging local communities through the unidimensional monetary system of value imposed on all areas of life. The research presented in this thesis is practice-based and is concerned with `finance art', which refers to art production using global finance as its medium. Finance art focuses on how artists use global finance techniques, tools, technology, innovation and methods as their medium to produce artworks that reveal the hidden layers of the complex systems that form global finance and the underlying financialization process, and how they engage their audience with this often esoteric and elitist systemic field, inviting the questioning of financial practices. This thesis is concerned with understanding finance using creative works to make this invisible processes visible. For this purpose, we are proposing a new term, `finance art , and presenting a double purpose methodology, which helps us understand finance through critical analysis and artmaking. This methodology is based on Deleuze and Guattari s philosophical concepts as well as my own experience of finance as a working practice. It is validated through a review of existing finance artworks by several artists for the critical analysis part, and through the creation of three of my own finance artworks, which are presented as case studies, for the art-making part. This methodology is intended to be applicable for both critics and artists. This thesis is composed of eight chapters, which in turn explore the process of financialization and its sub-processes which support the transformation of the global financial system; presents a methodology for critical analysis and art-making, which is based mostly on Deleuze and Guattari's philosophical concepts; covers a survey of representative finance artworks and practices using the methodology for critical analysis; presents three case studies of my finance artworks that illustrate and demonstrate finance art operations, current topics of investigation in global finance through appropriation, and the application of the methodology for art-making; and concludes with reflections on the research produced and opportunities for future work.
APPROVED
Keywords: Finance Art, Global Finance, Financialization, Deleuze, Guattari, Flash Crash, Ethical Recommender, Cryptocurrency, Blockchain, Securitisation, Artistic Research, Practice Based Research